2011
DOI: 10.1590/s0102-695x2011005000025
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of the genus Alpinia, Zingiberaceae

Abstract: Plants containing bioactive substances have increasingly become the object of research studies, particularly those plants with therapeutic value. Many species of the genus Alpinia provide a variety of medicinal properties, such as, Alpinia zerumbet (Pers.) Burtt et Smith and A. purpurata (Vieill) K. Schum, which have a significant presence in Brazil. These species have been commercialized in the food and cosmetic industries. However, their greatest importance arises from the medicinal properties of their essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 61 publications
0
27
0
4
Order By: Relevance
“…et Smith, also called Alpinia speciosa K. Schum is abundant in Northeast Brazil, where it is commonly known as "colônia". 1 The medicinal properties of this species are related to different parts of the plant, including leaves, flowers and rhizomes. 2 A field research conducted in Ibiúna, São Paulo, Brazil, revealed the use of A. zerumbet volatile fraction in respiratory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…et Smith, also called Alpinia speciosa K. Schum is abundant in Northeast Brazil, where it is commonly known as "colônia". 1 The medicinal properties of this species are related to different parts of the plant, including leaves, flowers and rhizomes. 2 A field research conducted in Ibiúna, São Paulo, Brazil, revealed the use of A. zerumbet volatile fraction in respiratory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…These species have been commercialized in the food and cosmetic industries. However, their greatest importance arises from the medicinal properties of their essential oils which have been used in folk medicine (Victório, 2011). Some studies have reported different pharmacological properties of the essential oil of A. zerumbet, such as antihypertensive (Lahlou et al, 2003), antinociceptive (de Araújo et al, 2005), anxiolytic (Satou et al, 2010), antipsychotic and antioxidant (de Araújo et al, 2011) attributes.…”
Section: Introductionmentioning
confidence: 99%
“…In folk medicine, A . zerumbet has a wide spectrum of traditional uses, ][ a fact that appears through its creole denominations ‘atoumo’ meaning ‘against all pains’, as well as ‘guérit‐tout’ meaning ‘cures everything’ . ][ Releasing a ginger‐like aroma, the rhizome is used notably as a tonic and a stimulant in various forms such as macerations, infusions, tinctures, etc …”
Section: Introductionmentioning
confidence: 99%
“…][ In Brazil, the tea made from A . zerumbet leaves is recommended as an antihypertensive medication and presents diuretic, spasmolytic, bacteriostatic/bactericide, fungistatic, anti‐inflammatory, antioxidant, and antiulcerogenic effects . ][ …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation